The success of technology transfer in the Industry 4.0 era: A systematic literature review - Razan Alkhazaleh; Konstantinos Mykoniatis; Ali Alahmer (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Modern innovative models have the possibility of transferring research and development (R&D) output through technology transfer from scientific and research institutions or other enterprises. The complex process of technology transfer is significantly dependent on cooperation among academia, industry, and governments (I4.0) in response to the technological developments driven together through Industry 4.0. As a result, numerous technology transfer factors must be addressed for I4.0 to become a reality. However, the abundance of literature on I4.0 and associated technologies, the key ingredients, and insights for effectively executing I4.0 technology transfer are fairly limited. This study focuses on the success factors of technology transfer for I4.0. The framework is based on systematic literature to outline significant results and factors. Furthermore, this study summarizes, analysis, and criticizes the actual models and their influential variables for I4.0 technology transfer. One of the findings of this study is the significance of cooperation between technology recipients, agents, and inventors for I4.0 technology transfer. Another impressive finding is the significance of the ecosystem component in technology transfer. Combining I4.0 technologies and open innovation is a game-changer, enabling businesses to significantly save time and cost. This article will assist decision-makers in developing policies and strategies to improve the I4.0 technology transfer process. Furthermore, this involves identifying the kind of government assistance that will help accelerate the transition to I4.0 via technology transfer.
Keywords: 650; barriers; industry 4.0; models; systematic literature review; technology transfer